2018
DOI: 10.3390/ijms19020635
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro Effects of Enzymatic Digested Gliadin on the Functionality of the Autophagy Process

Abstract: Gliadin, the alcohol-soluble protein fraction of wheat, contains the factor toxic for celiac disease (CD), and its toxicity is not reduced by digestion with gastro-pancreatic enzymes. Importantly, it is proved that an innate immunity to gliadin plays a key role in the development of CD. The immune response induces epithelial stress and reprograms intraepithelial lymphocytes into natural killer (NK)-like cells, leading to enterocyte apoptosis and an increase in epithelium permeability. In this contribution, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Finally, TG2 appeared to colocalize with the autophagic marker LC3 more in CD cells than in control ones. This finding could be related to the complex role of TG2 in regulating autophagy [33,34], a process that could contribute, if deranged, to CD pathogenesis [35,36].…”
Section: Discussionmentioning
confidence: 96%
“…Finally, TG2 appeared to colocalize with the autophagic marker LC3 more in CD cells than in control ones. This finding could be related to the complex role of TG2 in regulating autophagy [33,34], a process that could contribute, if deranged, to CD pathogenesis [35,36].…”
Section: Discussionmentioning
confidence: 96%
“…Albumin and casein (Sigma) were digested following the same protocol and were used as negative controls. PT-gliadin AlexaFluor555 labelling (GLIA-555) and purification was performed, as described previously [12], using affinity chromatography-purification G50 column (GE Healthcare, Little Chalfont, UK). The resulting labelled proteins were resuspended in PBS and labelled according to the manufacturer’s instructions with AlexaFluor555 using Alexa Fluor Microscale Labelling Kits (ThermoFisher, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, the intracellular accumulation of the gliadin peptide p31-43 leads to an increase in reactive oxygen species (ROS) levels [6], and the highly immunogenic 33-mer peptide is able to form supramolecular organized immunoreactive structures resistant to low pH [7,8,9]. Although autophagy dysregulation has been largely described in different autoimmune disorders affecting the intestine, such as inflammatory bowel diseases (IBDs) [10,11], little evidence was collected in our laboratory supporting the hypothesis that autophagy could play a role in CD pathogenesis [12,13]. A major reason to thoroughly investigate autophagy in the context of CD is that this cellular process is implicated in the oxidative stress response [14] and in protein aggregates degradation [15], as well as in the maintenance of the barrier function in the epithelial cells of the small intestine [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latest PubMed contribution, Manai and collaborators [36] reported that in Caco-2 cells, a widely used in vitro model for celiac disease studies, the administration of enzymatically digested gliadin (PT-gliadin) peptides significantly reduced the expression of the LC3-II autophagy-related marker. Furthermore, electron and fluorescent microscope analysis suggested a compromised function of the autophagosome apparatus.…”
Section: Autophagy and Celiac Diseasementioning
confidence: 99%